Aldehyde-mediated inhibition of asparagine biosynthesis has implications for diabetes and alcoholism - John, T; Saffoon, N; Walsby-Tickle, J; Hester, SS; Dingler, FA; Millington, CL; McCullagh, JSO; Patel, KJ; Hopkinson, RJ; Schofield, CJ (Royal Society of Chemistry, 2024)
Patients with alcoholism and type 2 diabetes manifest altered metabolism, including elevated aldehyde levels and unusually low asparagine levels. We show that asparagine synthetase B (ASNS), the only human asparagine-forming enzyme, is inhibited by disease-relevant reactive aldehydes, including formaldehyde and acetaldehyde. Cellular studies show non-cytotoxic amounts of reactive aldehydes induce a decrease in asparagine levels. Biochemical analyses reveal inhibition results from reaction of the aldehydes with the catalytically important N-terminal cysteine of ASNS. The combined cellular and biochemical results suggest a possible mechanism underlying the low asparagine levels in alcoholism and diabetes. The results will stimulate research on the biological consequences of the reactions of aldehydes with nucleophilic residues.